Effectiveness of Maternal Class Programme on Knowledge of Pregnancy Danger Signs: Efektifitas Program Kelas Ibu Terhadap Pengetahuan Tanda Bahaya Kehamilan - Kundaryanti, Rini; Dinengsih, Sri; Budiani, Neti (Jurnal Kebidanan Midwiferia, 2024)
The socialisation of the Pregnant Women's Class was conducted in 2008 but the implementation was in 2009, and it became one of the Health Office's programmes. Pregnant Mother Classes through face-to-face will provide opportunities for pregnant women to learn health issues such as health during pregnancy, childbirth, postpartum period, care for babies and birth certificates, and infectious diseases. This study was conducted to determine the effectiveness of the implementation of pregnant mother classes on knowledge of pregnancy danger signs at UPT Puskesmas Talegong Garut West Java 2023. This study used a pseudo-experimental design before and after in 2 groups with a sample of 72 respondents, consisting of 2 groups, namely 36 respondents in the intervention group and 36 respondents in the control group. Sampling method using random sampling technique. The research instrument used a questionnaire about the implementation of pregnant women's classes. The questionnaire has been tested to ensure its validity and reliability. Data were analysed with descriptive and Wilcoxon tests to determine the difference in knowledge scores between the 2 groups. There was a significant difference in knowledge score about pregnancy danger signs pretest and posttest in the intervention group (p-value 0.000). Conclusion: Maternal class is effective to improve the knowledge of pregnant women. Suggestion: It is expected that health services can improve maternal class services as an effort to prepare a healthy pregnancy.